Waqf Based Sustaining Entrepreneurship: An Analytical Mechanism (Malaysia Example): Kewirausahaan Berkelanjutan Berbasis Wakaf: Sebuah Mekanisme Analitis (Contoh di Malaysia) - Farra Munna Harun; Bayu Taufiq Possumah (Litera Academica Publishing, 2024)
Understanding entrepreneurship's role in the economy requires breaking down the concept itself. Entrepreneurship is crucial for growth and development, serving as a powerful tool for capacity building at both global and individual levels, ultimately driving economic progress. Sustainable financial mechanisms are essential for supporting initiatives that address socio-economic challenges faced by disadvantaged communities. One such financial mechanism in Islam is cash waqf, which is integral to the Islamic financial system. This paper analyzes how waqf funds can sustain entrepreneurship. Using qualitative methods, the study will explore the underlying reasons and mechanisms, aiming to provide innovative financial instruments through the waqf sector. The findings may offer valuable insights for government and private institutions, such as JAKIM and MAIS, to enhance economic development planning linked to entrepreneurship.